Strategic management of public and third sector organizations : a handbook for leaders - Nutt, Paul C.; Backoff, Robert W. (San Francisco, California : Jossey-Bass Inc., Publishers, 1992)
The Strategic management of public and third sector organization often poses "what" and "how" questions to managers who want to become strategic leaders. The "what" question concerns content. Strategic leaders want to know what a strategy looks like and how to use it to effect change in their organizations.
Part One. The Importance of strategy in then public and non-profit sectors -- Part Two. An overview of strategic concepts and issues -- Part Three. The Strategic management process -- Part Four. Useful support techniques -- Part Five. Strategy in practice: three cases.
Includes bibliographical references and index.
Keywords: PUBLIC SECTOR